PENGARUH GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN DENGAN TRANSPARANSI SEBAGAI VARIABEL PEMODERASI - Septiani, Diandra Putri; Khairunnisa, Khairunnisa (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The objective of this research is to investigate the impact of green accounting on financial achievement with transparency as a moderating variable. The population is metals and minerals sub- industry in the basic materials industry listed on the Indonesia Stock Exchange for the 2018-2022 period. The study applied a purposive sampling method so there are 90 samples of the metals and minerals sub-sector during study period. The analytical methods employed include simple linear regression and moderated regression analysis. The results showed that partially green accounting and transparency had a positive effect on financial performance. Other results showed that transparency can mitigate the impact of green accounting on financial performance. Simultaneously, green accounting and transparency had an influence on financial performance